An Experimental Investigation of Victim Blaming in Sexual Assault: The Roles of Victim Sexual Orientation, Coercion Type, and Stereotypes About Bisexual Women - Dyar, Christina (Journal of interpersonal violence, 2021)
Bisexual women are more likely to be sexually assaulted and to receive negative reactions to disclosures of sexual assault than heterosexual and lesbian women. However, few studies have examined the extent to which victim sexual orientation and related factors influence perceptions of sexual assault victims and perpetrators. To fill this gap, the current study used an experimental manipulation to examine the influence of victim sexual orientation and coercion type on perceptions of sexual assault victims and perpetrators. Participants (N = 826) were randomly assigned to read one of nine vignettes in which the sexual orientation of the female victim (bisexual, lesbian, heterosexual) and the type of coercion (verbal, physical, alcohol incapacitation) were varied. Then, participants were asked a series of questions about the victim and the perpetrator. Results indicated that bisexual and heterosexual female victims were both perceived as having wanted to have sex with the perpetrator more and as having “led the perpetrator on” more than lesbian victims. In contrast, victim sexual orientation was not associated with explicit ratings of victim or perpetrator responsibility or victim suffering. Bisexual female victims were also perceived as more promiscuous than both lesbian and heterosexual female victims. In turn, perceiving the victim as more promiscuous was associated with perceiving the victim as more responsible, having wanted to have sex with the perpetrator more, having “led the perpetrator on” more, and suffering less, and with perceiving the perpetrator as less responsible. In sum, our findings suggest that efforts to reduce sexual violence toward bisexual women should attend to negative attitudes toward bisexual women, especially the perception of bisexual women as promiscuous.